Instilling Ulul Albab Values ‘Spiritual Depth’ Through Conversational Texts in the Al Arabiya Lil Hayah Book - Kirom, Makhiulil; Qomari, Nur; Bakhiet, Bakri Mohommed (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Character is a reflection of the person; positive character reflects the positive values that one possesses. The attempt to teach this positive character continues, one of which is through Al Arabiyah's Lil Hayah textbook, which claims to contain the values of Ulul Albab. This research aims to analyze the Ulul Albab values contained in the text of the textbook's conversation and discuss them in depth. The Al Arabiya Lil Hayah book became the primary source of learning for students at one of the universities in East Java. This research uses a qualitative research method with a descriptive analysis of Harold D. Lasswell's approach to the Al Arabiya Lil Hayah textbook, 1st volume. The analysis is carried out systematically, objectively, and qualitatively. The analysis's findings demonstrate that Ulul Albab's values are distributed pretty equally across the textbook. It is seen from the text of the conversation that it contains spiritual values evenly and is designed to instill those values in the student's subconscious. This research contributes to the understanding of character development through Arabic textbooks. The results of this research can be beneficial to developers, teachers, and Arabic language learners to instill the spiritual depth values of Ulul Albab.